A theoretical study on the effects of thermal barrier coating on diesel engine combustion and emission characteristics. (1st November 2018) - Yao, Mingfa; Ma, Tianyu; Wang, Hu; Zheng, Zunqing; Liu, Haifeng; Zhang, Yan
Abstract: In recent years, thermal barrier coating (TBC) has been used as an effective way to reduce the heat transfer losses and to improve the thermal efficiency of internal combustion (IC) engine. In this study, a mathematic model has been proposed by taking the TBC material parameters into account, which is applied to explore the effects of TBC on engine combustion and emissions. Details of the combustion process is analyzed for the coated and uncoated engines under both low and high load conditions. The result shows that TBC has the ability of reducing wall heat transfer losses, thus improving the indicated thermal efficiency. A redistribution of different temperature regions is found with TBC and the coating shows better performance at rich mixture region due to higher temperature increase rate and at squish region due to higher surface/volume ratio. Both the soot oxidation process and NOx formation process are accelerated with TBC. However, TBC also enhances the overlap region between the high soot region and high temperature region, which accelerates the soot oxidation rate and greatly improves the soot emission. Highlights: A mathematical model of thermal barrier coating is proposed. Variation of in-cylinder combustion with TBC is analyzed in detail. TBC enhances the overlap between the high soot region and high temperature region.